2008
DOI: 10.1083/jcb.200710039
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial polarity requires septin coupling of vesicle transport to polyglutamylated microtubules

Abstract: In epithelial cells, polarized growth and maintenance of apical and basolateral plasma membrane domains depend on protein sorting from the trans-Golgi network (TGN) and vesicle delivery to the plasma membrane. Septins are filamentous GTPases required for polarized membrane growth in budding yeast, but whether they function in epithelial polarity is unknown. Here, we show that in epithelial cells septin 2 (SEPT2) fibers colocalize with a subset of microtubule tracks composed of polyglutamylated (polyGlu) tubuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
211
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(214 citation statements)
references
References 38 publications
2
211
0
1
Order By: Relevance
“…Cytoskeletal tracks can further be characterized by the alignment with small GTP-binding septins. Spiliotis et al have shown that septin-2 coupling of polyglutamylated microtubules to post-Golgi vesicle transport is required for the morphogenesis of polarized MDCK cells (Spiliotis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeletal tracks can further be characterized by the alignment with small GTP-binding septins. Spiliotis et al have shown that septin-2 coupling of polyglutamylated microtubules to post-Golgi vesicle transport is required for the morphogenesis of polarized MDCK cells (Spiliotis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The septin tracks also facilitate post-Golgi vesicle transport by antagonizing MAP4, which has an inhibitory role in vesicle transport. This regulatory step is required for columnar-shaped epithelial morphogenesis [Spiliotis et al, 2008].…”
Section: Epithelial Cell Polarizationmentioning
confidence: 99%
“…Septins were originally discovered in a screen for temperature-sensitive cell division mutants in yeast (Hartwell, 1971). There are 14 septin genes in humans (Hall et al, 2005;Peterson et al, 2007), which play roles in mitosis (Spiliotis et al, 2005), vesicle trafficking (Beites et al, 1999;Spiliotis et al, 2008) and membrane compartmentalization in specialized structures -such as the primary cilium (Hu et al, 2010;Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%